Function and Structure of Lacticaseibacillus casei GH35 β-Galactosidase LBCZ_0230 with High Hydrolytic Activity to Lacto-N-biose I and Galacto-N-biose - Saburi, Wataru; Ota, Tomoya; Kato, Koji; Tagami, Takayoshi; Yamashita, Keitaro; Yao, Min; Mori, Haruhide (Journal of applied glycoscience : JAG, 2023)
β-Galactosidase (EC 3.2.1.23) hydrolyzes β-D-galactosidic linkages at the non-reducing end of substrates to produce β-D-galactose. Lacticaseibacillus caseiis one of the most widely utilized probiotic species of lactobacilli. It possesses a putative β-galactosidase belonging to glycoside hydrolase family 35 (GH35). This enzyme is encoded by the gene included in the gene cluster for utilization of lacto-N-biose I (LNB; Galβ1-3GlcNAc) and galacto-N-biose (GNB; Galβ1-3GalNAc) viathe phosphoenolpyruvate: sugar phosphotransferase system. The GH35 protein (GnbG) from L. caseiBL23 is predicted to be 6-phospho-β-galactosidase (EC 3.2.1.85). However, its 6-phospho-β-galactosidase activity has not yet been examined, whereas its hydrolytic activity against LNB and GNB has been demonstrated. In this study, L. caseiJCM1134 LBCZ_0230, homologous to GnbG, was characterized enzymatically and structurally. A recombinant LBCZ_0230, produced in Escherichia coli, exhibited high hydrolytic activity toward o-nitrophenyl β-D-galactopyranoside, p-nitrophenyl β-D-galactopyranoside, LNB, and GNB, but not toward o-nitrophenyl 6-phospho-β-D-galactopyranoside. Crystal structure analysis indicates that the structure of subsite −1 of LBCZ_0230 is very similar to that of Streptococcus pneumoniaeβ-galactosidase BgaC and not suitable for binding to 6-phospho-β-D-galactopyranoside. These biochemical and structural analyses indicate that LBCZ_0230 is a β-galactosidase. According to the prediction of LNB's binding mode, aromatic residues, Trp190, Trp240, Trp243, Phe244, and Tyr458, form hydrophobic interactions with N-acetyl-D-glucosamine residue of LNB at subsite +1.